The Great War in history debates and controversies, 1914 to the present - Winter, Jay 1945-; Prost, Antoine 1933- (Studies in the social and cultural history of modern warfare, 2005)
Since the Armistice, a vast literature has been produced on the First World War and its repercussions. In this 2005 book, two leading historians from the United States and France have produced a fully comparative analysis of the ways in which this history has been written and interpreted. The book identifies three generations of historians, literary scholars, film directors and writers who have commented upon the war. Through a thematic structure, it assesses not only diplomatic and military studies but also the social and cultural interpretations of the Great War as seen primarily through the eyes of French, German and British writers. It provides a fascinating case study of the practice of history in the twentieth century and of the enduring importance of the national lens in shaping historical narrative. This interesting study will prove invaluable reading to scholars and students in history, war studies, European history and international relations